贸易和发展报告 2020 - United Nations Conference on Trade; Development (United Nations)
This report analyses the economic impacts of the Covid-19 (coronavirus) global pandemic and possible responses that could be both effective and inclusive. It examines different recovery scenarios and, in particular, highlights the danger of a lost decade, addressing immediate difficulties facing developing countries, as well as some of the underlying conditions that, if left unaddressed, will prevent a better recovery. It also discusses some of the institutional changes needed at the international level to bolster the recovery and the transition to a more socially-caring and environmentally-sustainable global economy – a transition that was needed before the pandemic and has become ever more pressing.